Contribution of MRI to the exploration of spinal pathologies in the medical imaging department of the CNHU/HKM in 2021 - ADJADOHOUN, SONIA B M G; ALIHONOU, THIERRY; AKANNI, DWMM; YEKPE AHOUANSOU, patricia; SAVI DE TOVE, KM; BIAOU, OLIVIER (My University, 2022)
Abstract Introduction: Radiological exploration of the spine and spinal cord is now well codified. Nevertheless, technical evolutions, in particular magnetic resonance imaging (MRI), allow new diagnostic avenues to be opened up and it is interesting to know what their place in clinical practice might be today. With the recent installation of the 1.5 Tesla MRI at the CNHU-HKM and with the aim of a preliminary evaluation of the activities, this work was carried out with the objective of studying the contribution of MRI in the exploration of cervical spinal pathologies at the CNHU-HKM of Cotonou. Materials and Methods: A prospective cross-sectional study with descriptive and analytical aims was carried out in the medical imaging department of the CNHU-HKM from June 1, 2021 to November 30, 2021 (6 months). All subjects referred to the MRI unit for cervical spine MRI were included. The parameters studied were the frequency of request for MRI, age, sex, clinical indication and MRI results. Results: 57 patients were collected. The frequency of requesting cervical MRI was 20.62% of all MRI examinations. The average age of the patients was 46.88 years, with extremes of 08 and 77 years. There was a male predominance with a sex ratio of 2.16. Cervicobrachial neuralgia (CBN) was the most frequent reason for requesting cervical MRI (38.6%). The abnormalities detected on MRI were degenerative in 84.2% of cases and traumatic in 8.8% of cases. Degenerative pathology was dominated by disc herniation (68.4%) and cervicarthrosis (61.5%). Spinal cord contusion (7%) was the most frequent traumatic injury. There was a statistically significant agreement between cervicobrachial neuralgia, cervical trauma and MRI result. Conclusion: MRI remains the examination of choice and is of considerable value in the exploration of cervical spinal pathologies. In most cases, it allows the lesion responsible to be identified and appropriate therapeutic decisions to be taken. However, access to the entire population remains limited.
Keywords: MRI; cervical spine; Benin